Ethical considerations in research when building predictive risk modelling in child and family welfare (Journal of Comparative Social Work, 2024)
This article presents and discusses ethical issues and implications in research when building a predictive risk model for potential use in Danish child and family welfare. The idea is to build a predictive risk model in order to study whether such a model can be valuable to child and family welfare services in the assessment of risk – aimed specifically at the decision-making process regarding notifications.Based on a framework developed especially for this field, we present and discuss ethical considerations, reflections and actions in relation to four main ethical principles: non-maleficence, autonomy, justice and explicability. We hope that our reflections on these ethical challenges can inspire research – and potentially also the field of practice  when taking a deep dive into the difficult field of digitalization in social work.